TCP/IP first-step - Sportack, Mark A. 4 0 16; 5 (Indianapolis, IN : Cisco Press, 2005)
Provides a non-technical explanation of TCP/IP, the official communications protocol of the Internet, explaining what it is, where it came from, and how it is used.
Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; TCP/IP (Computer network protocol);TCP/IP (Computer network protocol); 20; 2